2009
DOI: 10.1186/1471-2164-10-239
|View full text |Cite
|
Sign up to set email alerts
|

Co-evolution of genomes and plasmids within Chlamydia trachomatis and the emergence in Sweden of a new variant strain

Abstract: Background: Chlamydia trachomatis is the most common cause of sexually transmitted infections globally and the leading cause of preventable blindness in the developing world. There are two biovariants of C. trachomatis: 'trachoma', causing ocular and genital tract infections, and the invasive 'lymphogranuloma venereum' strains. Recently, a new variant of the genital tract C. trachomatis emerged in Sweden. This variant escaped routine diagnostic tests because it carries a plasmid with a deletion. Failure to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
152
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(169 citation statements)
references
References 45 publications
13
152
1
2
Order By: Relevance
“…Chlamydia trachomatis Sweden 2 (E/SW2), representing the Swedish nvCT (plasmid‐containing serovar E, with a 377‐base pair deletion in CDS1), was isolated from a male urethra in Malmö in 2006 (Seth‐Smith et al ., 2009; Unemo et al ., 2010). Chlamydia trachomatis Sweden, serovar F, plasmid‐free (F/SWFP−) is a cervical isolate from Malmö, Sweden, in 1995 (Persson et al ., 1996; Wang et al ., 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlamydia trachomatis Sweden 2 (E/SW2), representing the Swedish nvCT (plasmid‐containing serovar E, with a 377‐base pair deletion in CDS1), was isolated from a male urethra in Malmö in 2006 (Seth‐Smith et al ., 2009; Unemo et al ., 2010). Chlamydia trachomatis Sweden, serovar F, plasmid‐free (F/SWFP−) is a cervical isolate from Malmö, Sweden, in 1995 (Persson et al ., 1996; Wang et al ., 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Extraction of DNA was performed on strain F/SWFP− as previously described (Seth‐Smith et al ., 2009). DNA was sequenced on the Illumina GAII platform using 54‐bp paired‐end reads, resulting in a mean genome coverage of 1527 ×.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the plasmid p2TK2-SW2 (20) and the pBOMB4 series of plasmids (21) combined a ␤-lactamase-encoding gene (bla) and a multiple-cloning site into the L2 pSW2 and pL2 (L2/434/Bu) plasmids, respectively. The pBOMB4 series offers the additional benefit of utilizing an intact L2 plasmid (pL2) rather than the SW2 variant plasmid, which harbors a 377-bp deletion in CDS1 (148). These vectors are well suited for expressing epitope-tagged or untagged gene products under the control of native promoters.…”
Section: Ectopic Gene Expressionmentioning
confidence: 99%
“…Stable transformants lost their endogenous plasmid and expressed both the ␤-lactamase and chloramphenicol acetyltransferase genes, indicating that the standard E. coli promoters driving the expression of both drug resistance cassettes are functional in C. trachomatis. Subsequently, EBs were transformed with the hybrid shuttle plasmid pGFP::SW2, which consists of a variant L2 plasmid (pSW2) with a 377-bp deletion in CDS1, isolated from a Swedish LGV L2 clinical isolate (148), and an E. coli plasmid expressing ␤-lactamase and GFP fused to chloramphenicol acetyltransferase under the control of a Neisseria promoter. GFP-expressing bacteria within inclusions were readily detectable (19).…”
Section: Stable Plasmid Transformationmentioning
confidence: 99%
“…35 It is also known that the plasmid is not naturally transferred readily between clinical isolates supporting a host-plasmid tropism relationship. 36 This has been confirmed by recent experiments aimed at developing a transformation system for non-LGV isolates of the ocular tropic C. trachomatis serovar A where it was observed that stable plasmid transformants were only obtained when the transforming plasmid shuttle vector was matched with the parental strain. 37 More recently, transcriptional profiling of cultured human epithelial cells infected with plasmid-deficient and -proficient C. trachomatis organisms has revealed statistically significant increases in the levels of expression of host genes coding for proinflammatory, immune suppression, and cell growth and fibrosis proteins in plasmid-bearing strains.…”
Section: Chlamydial Plasmidmentioning
confidence: 52%